2011
DOI: 10.1098/rspa.2011.0097
|View full text |Cite
|
Sign up to set email alerts
|

Recovery by triple junction motion in aluminium deformed to ultrahigh strains

Abstract: Commercial purity aluminium at true strains 3 = 2 ∼ 5.5 was annealed in a wide temperature range (from room temperature to 220• C), and the evolution of microstructure was characterized using transmission electron microscopy (TEM) and electron backscattered diffraction (EBSD) techniques. Triple junctions in an ultrafine lamellar structure are classified into three categories based on the structural morphology, and a relationship is formulated between the density (length per unit volume) of triple junctions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 35 publications
4
65
0
Order By: Relevance
“…4a). As triple junction migration has been proposed as an important recovery mechanism for lamellar structure composed of mainly high angle boundaries [15,16], the presence of high angle boundaries in HMRs should have the chance of forming mobile Y-type tripe junction that is composed of three lamellar boundaries with medium to high misorientation angle [15]. Such triple junction was observed in the boundary sketch of Figure 2b, which is composed of three boundaries that are misoriented by 53.45 o , 15.2 o and 53.6 o , respectively.…”
Section: Hmrsmentioning
confidence: 99%
“…4a). As triple junction migration has been proposed as an important recovery mechanism for lamellar structure composed of mainly high angle boundaries [15,16], the presence of high angle boundaries in HMRs should have the chance of forming mobile Y-type tripe junction that is composed of three lamellar boundaries with medium to high misorientation angle [15]. Such triple junction was observed in the boundary sketch of Figure 2b, which is composed of three boundaries that are misoriented by 53.45 o , 15.2 o and 53.6 o , respectively.…”
Section: Hmrsmentioning
confidence: 99%
“…Direct quantitative comparison among the sequential EBSD maps, for example to measure local boundary migration distance during annealing [17], is rather difficult because of the distortion. As a result, although many in-situ and ex-situ studies have been conducted in the last decade, in most cases only qualitative analysis has been reported [18,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Even more frequently, an EBSD map has to be compared with other EBSD maps of the same series collected during in-situ and ex-situ experiments [18][19][20][21][22][23]. In these cases, the coordinates in each of the EBSD map can be distorted relatively to the others because non-constant drift typically leads to different distortion among the series.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5a shows no obvious change in the lemallar morphology in both the deformation zone and the matrix region after annealing for 1 hour at 150℃ as compared with the deformed state ( figure 1b). However, quantification of lamellar bounadry sapcings showed that structural coarsenng has taken place by triple junction motion as observed in aluminum of commecial purity [11,12]. Enhanced recovery in the deformatin zone around the large Si particle is seen after annealing for 1 hour at 200℃ , figure 5b-c.…”
Section: Recovery Of the Deformation Zone Around Large Si Particlesmentioning
confidence: 88%